2022
DOI: 10.1029/2022jd037048
|View full text |Cite
|
Sign up to set email alerts
|

What Controls the Skill of General Circulation Models to Simulate the Seasonal Cycle in Water Isotopic Composition in the Tibetan Plateau Region?

Abstract: This study evaluates the simulation of the seasonal cycle of water isotopic composition over Tibetan Plateau regions (TP) from six isotope‐enabled general circulation models (GCMs) participating in the second Phase of Stable Water Isotope Intercomparison Group. For both meteorological factors (precipitation rate and wind field) and isotopic composition, GCMs generally agree with reanalysis data and in‐situ observations, but there is a significant spread across models and the isotopic seasonality is systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 135 publications
2
2
0
Order By: Relevance
“…The difference in the range of variations (between observed and model values) is clearly evident in the frequency distribution of δD values (Figure 5). The negative isotope biases in the models during the ISM have also been reported in a few earlier studies [26,28,50]. In our earlier study [27], we identified that the underestimation of the mean isotope values can be due to (a) an inaccurate vapour isotope profile and (b) a lower estimate of the raindrop evaporation.…”
Section: Comparison Between Observed and Model Rain Isotope Valuessupporting
confidence: 84%
See 2 more Smart Citations
“…The difference in the range of variations (between observed and model values) is clearly evident in the frequency distribution of δD values (Figure 5). The negative isotope biases in the models during the ISM have also been reported in a few earlier studies [26,28,50]. In our earlier study [27], we identified that the underestimation of the mean isotope values can be due to (a) an inaccurate vapour isotope profile and (b) a lower estimate of the raindrop evaporation.…”
Section: Comparison Between Observed and Model Rain Isotope Valuessupporting
confidence: 84%
“…The limited available studies dealing with the performance of the GCMs over the Asian monsoon region show that two nudged models-LMDZ4 and IsoGSM Nudged [26][27][28] -perform better over these regions. The other models, in contrast, show large biases in various physical fields like temperature, humidity, wind etc., both in monthly and seasonal scales.…”
Section: Study Area and Choice Of Gcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest and most commonly used intercomparison simulation data set is the SWING phase 2 (Risi et al., 2012). This data set has supported numerous studies that interpret measured isotope observations or compare those findings with other models (Conroy et al., 2013; S. Dee et al., 2015; Hu et al., 2018; Shi et al., 2022). However, simulations under this framework have not been nudged using consensus reanalysis data sets, and some results were free‐running simulations that followed the experiment design for the comparison of Atmospheric Model Intercomparison Project simulations (Gates, 1992).…”
Section: Introductionsupporting
confidence: 76%
“…However, the spatial resolutions of climate models are usually coarse, and many topography-related information is smoothened. The performances of prediction models vary greatly in large spatial scale, with usually good performance in plain areas and poor simulation in complex terrains [18,19], indicating the importance of altitude correction of precipitation isotopes especially in a complex topography with large altitude fluctuation [20,21]. Compared to some global or regional long-term mean products of precipitation isotopes [22][23][24], the climate-model-derived simulation should be improved in spatial resolution, especially in small-scale cases with complex terrain, where altitude correction or downscaling is crucial for climate-model-simulated isotope data.…”
Section: Introductionmentioning
confidence: 99%